2020
DOI: 10.1016/j.foodchem.2019.125418
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and hydration in spray-dried milk protein powders: Selected physicochemical properties

Abstract: Water sorption and hydration in spray-dried milk protein powders: selected physicochemical properties, Food Chemistry (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
(56 reference statements)
6
18
0
1
Order By: Relevance
“…(Note: Lactose crystallisation, which is an important factor to consider in relation to the solubility of the MPC powders, did not occur in the current study (results not shown). Maidannyk [24] reported that MPC powders, ranging in protein content from 40-80% (w/w), did not show lactose crystallisation in their amorphous state following spray drying, but this process did occur for MPC40, 50, and 60 powders stored at high relative humidity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Note: Lactose crystallisation, which is an important factor to consider in relation to the solubility of the MPC powders, did not occur in the current study (results not shown). Maidannyk [24] reported that MPC powders, ranging in protein content from 40-80% (w/w), did not show lactose crystallisation in their amorphous state following spray drying, but this process did occur for MPC40, 50, and 60 powders stored at high relative humidity).…”
Section: Discussionmentioning
confidence: 99%
“…Milk protein concentrate (MPC) powders were produced in the Bio-functional Food Engineering Facility at Teagasc Food Research Centre (Moorepark, Fermoy, Co. Cork, Ireland) using a similar method as that described by Maidannyk [24]. Liquid MPC (19.5 and 16.6% w/w, total solids, and protein, respectively; i.e., MPC85) and concentrated milk permeate (24% w/w, total solids) were obtained from a local dairy supplier directly after ultrafiltration (UF) and reverse osmosis, respectively.…”
Section: Manufacture Of Milk Protein Concentrate Powdersmentioning
confidence: 99%
“…Milk protein is characterized by much better assimilability compared to cocoa, which translates into increased nutritional importance of this protein in the diet of the consumer [27,28]. According to Maidannyk, et al [29], milk powder proteins are susceptible to caking and adhesion and may be highly insoluble. Therefore, storage conditions of the powder are an important factor responsible for such problems.…”
Section: Introductionmentioning
confidence: 99%
“…The two higher protein powders showed larger final increases in mass (31.0% and 31.7% increase for the WPC 65 and 50, respectively) compared to the lower protein powders (20.7% and 19.8% increase for the WPC 35 and 20, respectively). Shrestha et al [30] and Maidannyk et al [33] reported similar results for a range of SMP/lactose mixtures and milk protein concentrate (MPC) powders, respectively. At RH < 40%, moisture absorption was primarily determined by the protein content of the powder, with the WPC 65 absorbing the most moisture.…”
Section: Moisture Sorption Isothermsmentioning
confidence: 78%
“…At RH < 40%, moisture absorption was primarily determined by the protein content of the powder, with the WPC 65 absorbing the most moisture. Lactose crystallization is evident in the isotherms for the WPC 20 and 35 by a decrease in the mass of the powders, which occurs due to the release of moisture during crystallization [12,15,[33][34][35][36]. Lactose crystallization also occurred at a higher RH for the WPC 35 (~70% RH) compared to WPC 20 (~60% RH), due to the competitive/preferential sorption of water by proteins, delaying the onset of crystallization [12,14,30,34].…”
Section: Moisture Sorption Isothermsmentioning
confidence: 99%